The political economy of the Gauteng City-Region - Greenberg, Stephen (My University, 2010)
The Gauteng city-region (GCR) is a relatively new concept for South Africa, although the model has been growing in other parts of the world for over a decade. This paper considers some of the global debates about the importance of city-regions in the current economic and political context. It provides an overview of the concept and the context within which it has been deployed. Debates about the role of cities in the global economy are regarded. Some critical reflections on the city-region, both conceptually and in practice, are made along economic, social, ecological and governance dimensions. This forms the backdrop for an analysis of the growth of the GCR, again both conceptually and practically along the same dimensions, with an emphasis on two key drivers of the city-region, transportation and housing/settlement.
Keywords: political economy, Gauteng, city-region